Schwann cells in regeneration and cancer - Zhang, Lan; Xie, Jiale; Dai, Wenyu; Lu, Bing; Yi, Sheng (Frontiers in Pharmacology, 2025)
Schwann cells are specific peripheral glial cells with remarkable plasticity following peripheral nerve injury. Injury responses stimulate c-Jun activation in Schwann cells, drive epithelial-mesenchymal transition and cellular phenotypic changes, and induce the generation of reprogrammed repair Schwann cells to orchestrate peripheral nerve regeneration process. Schwann cells and/or Schwann cell-derived molecules are commonly used as supporting cells and/or neurotrophic factors to construct Schwann cell-based tissue-engineered nerve grafts for repairing severe peripheral nerve injury with long defects. Transplantation of Schwann cells and/or Schwann cell-derived molecules also serves as a helpful approach for the treatment of other injured tissues, such as the spinal cord, skin, digit tip, and bone. Schwann cells are not only associated with tissue regeneration but also involved in tumorigenesis and tumor progression. Schwann cells are the major cellular component of neurofibromatosis type 1 and the sole cell type in neurofibromatosis type 2 and schwannomatosis. In addition, Schwann cells also function as an important player in the tumor microenvironment and aid in the growth and invasiveness of many other solid cancers. In the present review, we outline the physiological and pathological activities of Schwann cells and discuss the functional roles of Schwann cells in homeostasis, regeneration, and cancer.